2016
DOI: 10.2116/analsci.32.1237
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Trace Elements in Silicate Glass Sample by LA-ICP-QMS/QMS with an ORC: Silicon as the Matrix of Calibrating Solutions and the Internal Standard for Measurement

Abstract: A strategy was presented for quantitative analysis of trace elements in a glass sample by laser ablation inductively coupled plasma tandem quadrupole mass spectrometry (LA-ICP-QMS/QMS) with an octapole reaction cell (ORC). Silicon in the glass was used as the internal standard as well as the matrix for making the calibrating solutions. Sample aerosols generated by the laser ablation system were introduced into the dual pass spray chamber through the make-up gas port. Calibrating solutions were nebulized into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Zhu developed a strategy for the quantitative analysis of trace elements in a glass sample using laser ablation inductively coupled plasma tandem quadrupole mass spectrometry (LA-ICP-QMS/QMS) with an octapole reaction cell (ORC) 24) . In these studies, application of the proposed method was limited to certiˆed reference material sand not expanded to general glass samples which are typical sources of glass fragments in trace physical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu developed a strategy for the quantitative analysis of trace elements in a glass sample using laser ablation inductively coupled plasma tandem quadrupole mass spectrometry (LA-ICP-QMS/QMS) with an octapole reaction cell (ORC) 24) . In these studies, application of the proposed method was limited to certiˆed reference material sand not expanded to general glass samples which are typical sources of glass fragments in trace physical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Such an additional apparatus might cause a longer wash-out time due the memory-effect. As an alternative approach, the present authors had reported a method using a matrix-matched standard solution for quantitative analysis of trace elements in glass, 28 in which the sample aerosol from a makeup gas port was mixed with the solution mist generated by a nebulizer in the spray chamber, and then introduced into the ICP torch. In comparison to the conventional method, it has a superior signal stability and a simplified structure.…”
Section: Introductionmentioning
confidence: 99%